PENGARUH PENDAPATAN ASLI DAERAH, DANA ALOKASI UMUM, PDRB TERHADAP BELANJA DAERAH DAN INDEKS PEMBANGUNAN MANUSIA - Made Heny Urmila Dewi, Agung Ayu Putrisandya (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2021)
The purpose of this research is to analyze the influence of Local Own Revenue, General Allocation Fund, Gross Regional Domestic Product on Regional Expenditure and Human Development Index. This research was conducted in 9 districts/cities of Bali. This study uses path analysis techniques. Based on the analysis of statistical results, it can be concluded (1) local revenue and general allocation funds positively and significant affect the regional spending, the gross regional domestic product directly has a negative and insignificant effect on regional spending in the district/city of Bali. (2) Local revenue and gross regional domestic product positively and significant affect the human development index, the general allocation funds positively and insignificant affect the human development index, Regional expenditure negatively and significant affect the human development index in the Regency/City of Bali. (3) Regional expenditure is not an intervening variable of the local revenue’s effect, general allocation funds, and gross regional domestic product on the human development index in the regencies/cities of Bali.